A Review of Islamic Law on Community Traditions on the Prohibition of Marriage in the Month of Muharram (Case Study in North Galesong District, Takalar Regency) - Aisyah, Aisyah; Abbas, Abbas; Muntadzar, Ahmad (Family Law Study Program (Ahwal Syakhshiyah), Universitas Muhammadiyah Makassar, 2024)
In North Galesong sub-district, Takalar regency, there is a custom that although some people have abandoned it, there are still some who follow this traditional custom. Tradition in North Galesong sub-district of Takalar district links the time of the month of Muharram with the time of marriage. According to the words of the previous parents, the month of Muharram is a bad month for marriage, known as bulang bambang. Whereas in Islamic law there is nothing that explains the existence of bad times in the implementation of marriage. This type of research is qualitative research. It can be concluded that: 1). The impermissibility of holding a wedding in the month of Muharram in North Galesong sub-district of Takalar regency is a custom left by previous parents. The impermissibility of holding a wedding in the month of Muharram is still followed by some people. The month of Muharram is commonly referred to as bulang bambang by people in North Galesong sub-district, Takalar regency, because this month, according to previous parents, there were many bad events that occurred so that previous parents attributed it was not good to hold a wedding in the month of Muharram. 2). The tradition of not being allowed to hold a wedding in the month of Muharram in North Galesong sub-district of Takalar district in Islamic law can be said that choosing a good time to hold a contract / marriage is okay because in the case of muamalah including cultural traditions the law changes as long as there are no deviations, but considers that the month of Muharram is a bad month for holding a marriage including bad deeds to Allah Almighty. In this case Islam came to strengthen tawhid our belief that everything happens by the will of Allah Almighty. In Islamic law, a person may enter into marriage if the pillars and conditions have been fulfilled and do not violate the provisions of marriage.